Money on the Table? Firms' and Workers' Gains from Productivity Spillovers through Worker Mobility - Andrey Stoyanov; Nikolay Zubanov (Institute for the Study of Labor (IZA), 2013)
We estimate how much of the gains from productivity spillovers through worker mobility is retained by the hiring firms, by the workers who bring spillovers, and by the other workers. Using linked employer-employee data from Danish manufacturing for the period 1995-2007, we find that at least two-thirds of the total output gain of 0.11% per year is netted by the firms, while the workers who bring spillovers receive at most 6% of it as the wage premium. The large share retained by the firms implies that spillovers through worker mobility are mostly a positive externality to them.
Keywords: D24; J31; J60; 330; productivity spillovers; worker mobility; wages; matched employer-employee data